A concave-convex design strategy for periodic self-locked energy-absorbing systems. (May 2023) - Liu, Haochuan; Qiao, Chuan; Ma, Yong; Pan, Fei; Chen, Yuli
Highlight: A concave-convex design strategy of self-locked systems is proposed. The self-locking principle of existing self-locked systems is summarized. Multiple self-locked systems are designed with the proposed design strategy. Self-locking performance of our design strategy is validated by FEM and experiment. Self-locked systems have better energy-absorbing performance than unlocked systems. Abstract: Metallic thin-walled tube systems are widely used in the field of impact protection. In particular, self-locked systems can be rapidly assembled for emergent energy absorption without the need of additional constraints. However, most of the existing self-locked systems are inspiration-based, indicating the lack of unified design guidance for self-locked systems. To expand and vivify the application of self-locked energy-absorbing systems, this paper proposes a universal design strategy that utilizes concave-convex features to enable periodic self-locking in desired directions. With this strategy, varieties of self-locked systems have been obtained for uni-, bi-, and tri-directional self-locking. Finite element simulations are used to characterize the self-locking and energy-absorbing performance of a representative bi-directional self-locked system in comparison with an unlocked system. The representative self-locked system can successfully resist lateral splash upon impact in the main direction, exhibiting better energy absorption performance than the unlocked system. To demonstrate the validity of the concave-convex design strategy, a drop weight impact test has also been performed on a paper prototype of the representative self-locked system, where 95.9% of the impact energy is absorbed by the self-locked system with no self-locked units splashing in the self-locking directions. This work provides a broad prospect for the design and application of self-locked energy-absorbing systems. Graphical abstract: Image, graphical abstract